PENGARUH LATIHAN MOVING TARGET TERHADAP PUKULAN FOREHAND DRIVE PADA KLUB TENIS BHINEKA BUNGO - Hasnah (Jurnal Muara Olahraga, 2023)
Abstract This research started from the existence of several problems, namely the Bhineka Tennis Club Bungo players still had deficiencies in hitting Forehand drives. This can be seen when practicing or playing when the enemy gives the ball towards the forehand, the Bungo Tennis Club's Bhineka Tennis players often make mistakes or die alone. This study aims to determine whether there is an effect of Moving Target Exercise on Forehand Drive Shots at the Bhinika Bungo Tennis Club. This type of research is an experiment with the design "The One Group Pretest-Postest Design". The population in this study were 28 Bhineka Bungo Tennis Club players and 12 people as samples. The sampling technique uses Purposive Sampling. The method used in this study is an experimental method that uses hypothesis testing, namely the T-test. This research was conducted at the Bungo Regency Pujasera Tennis Court at the Bhineka Bungo Tennis Club. The results of the research show that the Tcount value is 3.195 and the Ttable value is 2.200, so Tcount > Ttable is 3.195 > 2.200, this means that the hypothesis H1 is accepted and H0 is rejected. Thus it can be concluded that this study has the effect of the Moving Target exercise on Forehand Drive shots at the Bhineka Bungo Tennis Club. Keywords: Moving Target, Forehand Drive in Tennis